Office of Park Commission, New Bedford, Mass., Park Ordinances 74-75 (1902) - (:unkn) unknown (My University, 1902)
3. To throw stones, balls or other missiles; to discharge or carry firearms, firecrackers, torpedoes or fireworks; to make fires, to play musical instruments; to have for sale or otherwise any intoxicating liquors or beverages; to sell or offer for sale any goods or wares; to post or display signs, placards, flags or any advertising devices whatsoever; to play games of chance or to have possession of instruments of gambling; to utter profane, threatening, abusive or indecent language; to make orations or loud outcries; to in any manner annoy other visitors.
Keywords: DISCHARGE